Manufacturing “realities”. The impact of AI in the age of disinformation - Farcaș, Ioan-Claudiu (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales, 2025)
This paper examines the effect of generative artificial intelligence (AI) on propaganda, which has produced a significant shift from traditional methods. Twentieth-century propaganda was based on simplified driven narratives for mass audiences. AI expands the horizon, allowing for the creation of hyper-personalized disinformation at a very large scale. The analysis focuses on the relationship between AI-based bot networks and the algorithms behind social media platforms. It shows how these tools are actively deployed to suppress votes, discredit opponents, strengthen extremist movements, and fuel social polarization. To address this complex threat, a counterstrategy involving multiple stakeholders (governments, tech companies, civil society) is proposed as a way to shift from a reactive posture to a proactive strategy focused on shaping long-term societal resilience.